Social Interaction Role in Islamic Education: (Study of Sayyidati Aisyah RA Figure) - Qurrotul Ainiyah; Nur Ainun Nadhiroh (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2018)
Sayyidati Aisyah is as a wife, a hadits narration, educator, a religion instructor, and a smart student in various fields. Without abandoning her motherly, she was also able to communicate and interact with society. And the effect of her capability to interact with society had made her successful in education field. This research is about Sayyidati Aisyah’s role in interacting with society and her success in conducting multi roles in her time. This article is library research, in which the researcher collected data from literatures with academic standard. In analyzing the data, the researcher used descriptive analytical method, comparison with socio-historical approach and content analysis. The research result shows that Sayyidati Aisyah RA is Allah servant who is loyal, a Prophet wife; a religion instructor, a hadits narration, Muslim educator had an important role, and contributes greatly to the struggle and development of Islam. The success of the Islamic education process is marked by the realization of the educational goal, namely the existence of perfect human beings (kaffah), this is supported by the fulfillment of 5 elements; educator, students, material/curriculum, method, and environment. Educators and students, in interacting, have to carry out their role and function based on their status and position, the material of interaction, implementing the method in accordance with individual or other group in the interaction, understanding the environment condition.